Sound velocity profile (SVP) data for calibration of the EM 122 multibeam system of RV SONNE during cruise SO265 - Antje Dürkefälden; Jörg Geldmacher; Reinhard Werner (PANGAEA, 2022)
Four sound velocity profiles (SVP) were conducted during RV SONNE cruise SO265 that took place between 2018-08-26 and 2018-10-11 as part of the research project Shatsky Evolution. A CTD (conductivity, temperature, depth) rosette sampler was used for three profiles and a sound probe for the fourth profile and the probes were lowered down to 2000 m water depth. The data were used to calibrate the ship extquotesingles own EM 122 multibeam echo-sounder system.